factorise 6 minus x minus x square
Answers
Answered by
5
xsquare - x - 6
xsquare+3x square-2x square - 6
x (x-3)+2 (X-3)
(x+2) (x-3)
x=-2 x=3
hope it will help u
Answered by
2
the final answer is x=3 and x=-2
hope it helps you
please mark as the brainlist...♥️
hope it helps you
please mark as the brainlist...♥️
Attachments:
![](https://hi-static.z-dn.net/files/db9/50ab4aa4c3c2894ed2a3631b4ba3fcb1.jpg)
Similar questions
Social Sciences,
7 months ago
English,
7 months ago
Physics,
1 year ago
English,
1 year ago
Math,
1 year ago